Effect of nucleating agents on crystallinity and properties of poly (lactic acid) (PLA). (August 2017) - Aliotta, Laura; Cinelli, Patrizia; Coltelli, Maria Beatrice; Righetti, Maria Cristina; Gazzano, Massimo; Lazzeri, Andrea
Graphical abstract: Highlights: Two nucleating agents (LAK and PDLA) were tested for PLA in variable amounts. The two different nucleating agents both promote the α-form of PLA at 105 and 120 °C. The efficiency of PDLA as nucleant is higher with respect to LAK. Takayanagi's model was successfully applied to PLA. The elastic moduli of the amorphous and the α-crystalline phases were determined. Abstract: Polylactide (PLA) is one of the most promising biobased, compostable polymer able to replace petro-derived polymer not just in single use applications but also for durable equipment requiring more demanding technical performances, in particular in terms of mechanical properties and stability. In order to stabilize the material and improve mechanical properties, it is important to control the crystallinity grade in the polymer and at this purpose, the use of nucleating agents is an efficient approach. In the present work two nucleating agents (LAK301 and PDLA) of PLA were tested in variable amounts. The blends were processed by injection moulding at two different temperatures of the mould, 105 °C and 120 °C, respectively. At these temperatures, exclusively α-form grows in the investigated blends, as attested by X-ray diffraction measurements. For the first time the Takayanagi's model was applied to PLA, to correlate Young's modulus with the crystallinity degree. Good correlation was achieved between the model and the experimental data, allowing the calculation of the elastic modulus of the amorphous phase and the α-crystalline phase of PLA separately.